PENGARUH SURPLUS ARUS KAS BEBAS, KUALITAS AUDIT, LEVERAGE, UKURAN PERUSAHAAN, DAN ARUS KAS RELATIF TERHADAP MANAJEMEN LABA - Fariska Yonsa Ronikusuma; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2018)
Disclosure of information on corporate profits is often manipulated by company managers for their own benefit. High cash receipts and low expenditures become a profitable difference in the company's cash flow statement, the more vulnerable there is fraud committed by internal parties. The free cash flow or known as the free cash flow surplus for the company is for the development and reserves for repayment of debt that has not been repaid but is different from the objective of the investor as an additional return on the investment they give to the company, with this difference will lead to more imbalanced information given by the company to investors. To prevent fraudulent cash flow surpluses from occurring freely, an independent committee was formed whose purpose was to audit the performance of earnings management. This study aims to determine the magnitude of the effect of free cash flow surplus and auditor quality used with Big4 and Non Big4 audit measures, leverage, company size and relative cash flows from all mining sector companies that are now the trend of conversation in various corruption cases on earnings management in Indonesia.This research uses purposive sampling technique with a sample of 26 mining companies for 4 years and produces 104 financial reports recorded and registered on the Stock Exchange in 2013 to 2016. The data that has been obtained is then analyzed with several tests namely, descriptive statistical test, assumption test classic, multiple regression analysis, moderate multiple linear regression (residual test) using IBM SPSS 22 software application.The results of this study indicate that the free cash flow surplus has a positive and significant effect on earnings management. On audit quality has a negative influence on earnings management and firm size which has a significant positive effect on earnings management, but not with leverage and relative cash flows that have no effect.